THE USE OF THE WMA METHOD PREDICTS THE INVENTORY OF TOFU RAW MATERIALS CASE STUDY INDUSTRY TAHU IYUS - Desy Julika Sari; Herman Saputra; Akmal Nasution (Informatika, Universitas Jenderal Soedirman, 2022)
Industry Tahu Iyus is a business engaged in the industrial sector, this business makes white tofu and fried tofu. The problem that occurs in the Industry Tahu Iyus is that it is still difficult to determine the amount of tofu raw material inventory for the next month and experiencing an excess of tofu raw materials if this continues, the Industry Tahu Iyus will experience losses, one of the raw materials will be damaged and will experience a bad smell to the raw materials. The purpose of this research is to be able to build a forecasting system for the inventory of tofu raw materials in the Industry Tahu Iyus using previous data. The method that can be used in this study to predict the inventory of tofu raw materials is the Weighted Moving Average method, because this method is able to provide predictions by utilizing previous data and each data is given a different weight. This study applies the Weighted Moving Average method to obtain accurate forecasting results so as to minimize errors between forecasting and inventory reality, and is applied to a forecasting system for tofu raw material inventory per month with forecasting results for the following month, namely 4.150 Kg with a MAPE value of 6.54%.